Pengembangan Instrumen Konsep Diri dalam Manajemen Waktu Pada Siswa Kelas XI Sekolah Menengah Kejuruan - Iqbal Zakki Jannati; Nyoman Dantes (Jurnal Educatio: Jurnal Pendidikan Indonesia)
The purpose of this study: to determine the validity of the self-concept scale for time management in class XI students of SMK Negeri 1 Singaraja. Using a stratified random sampling technique and to determine the reliability of the items in the self-concept instrument in time management in class XI students of SMK Negeri 1 Singaraja. This study uses research and development methods (Research & Development). The validity test involved 5 experts, 3 guidance counseling lecturers and 2 practitioners counseling teachers at Vocational High Schools. The sample was selected 100 class XI students from a total of 1129 students of SMK Negeri 1 Singaraja. The results of this study are the low intelligence of time management in students and the inadequate availability of instruments in schools. The results of the CVR calculation obtained ∑CVR with the number 34.8. So it can be concluded that 34.8 > 0, which means that the contents of the interpersonal intelligence scale items fulfill the criteria (valid). The results of the CVI calculation obtained a result of 0.96 which included very suitable criteria.